Primary School Teachers' Opinions on the Difficulties They Experience Compared to Subject Teachers - DOĞAN , Adem; KÜTÜKÇÜ, Serap (Journal of Ecohumanism, 2024)
This study aims to determine the opinions of primary school teachers regarding the difficulties they experience compared to branch teachers. The research was conducted using a case study, one of the qualitative research methods. 25 primary school teachers participated in the study. A semi-structured interview form prepared by the researcher was used to obtain the data. Content analysis method was used in the analysis of the data. As a result of the research, it was determined that the biggest difficulty experienced by primary school teachers in classroom management compared to branch teachers is that they have difficulty in classroom management due to the young age of the students; according to the opinions of primary school teachers, the biggest difficulty experienced by branch teachers in the teaching process is taking on the responsibility of more lessons. It was determined that primary school teachers establish deeper and stronger emotional bonds with their students compared to branch teachers; they are divided into two in terms of being advantageous in terms of salary and additional lessons; and the majority of primary school teachers see themselves as disadvantaged due to working in villages and rural areas in terms of the settlement where they work compared to branch teachers.